Cleaner conversion of bamboo into carbon fibre with favourable physicochemical and capacitive properties via microwave pyrolysis combining with solvent extraction and chemical impregnation. (1st November 2019) - Lam, Su Shiung; Azwar, Elfina; Peng, Wanxi; Tsang, Yiu Fai; Ma, Nyuk Ling; Liu, Zhenling; Park, Young-Kwon; Kwon, Eilhann E.
Abstract: Bamboo was converted into carbon fibre using a novel approach combining microwave pyrolysis, solvent extraction, and chemical impregnation. The employment of solvent extraction and chemical impregnation transformed natural bamboo into bamboo fibre with yield of 64 wt% that comprised of 87 wt% cellulose, 4 wt% lignin and 9 wt% hemicellulose deemed desirable for conversion into carbon fibre. The subsequent use of microwave pyrolysis transformed the bamboo fibre to form carbon fibre; the effects of microwave irradiation time and microwave power (two key process parameters) on properties of carbon fibre were investigated. Microwave pyrolysis provides a rapid heating rate (30 °C/min) with relatively shorter process time (20 min) compared to that performed by conventional pyrolysis method, thus leading to a relatively lower electric consumption and providing a potentially cost-saving and energy-efficient approach to produce carbon fibre. The production and properties of carbon fibre produced were affected by irradiation time and microwave power. The carbon fibre obtained was detected to have high fixed carbon (80 wt%), carbon element (87%), high BET surface area (475 m 2 /g) and fibres in small diameter (≤1 μm). It also shows desirable features comprising low content of moisture (<6 wt%), inorganic elements of Na, K, S, Mg (≤5%) and ash (1 wt%), allowing the carbon fibre to have more active sites and making it a cleaner product rather than polluting the environment whereas a high ash content could lead to undesired catalytic reactions and emission of potentially hazardous metallic components present in the ash. Combined with the detection of positive capacitive behaviour, the carbon fibre shows great potential to be used as an electrode for energy storage application. The results disclose that microwave pyrolysis combining with solvent extraction and chemical impregnation can be a cleaner approach to transform bamboo into carbon fibre with favourable physicochemical and capacitive properties. Graphical abstract: Image 1070420 Highlights: A new approach combining microwave pyrolysis, solvent extraction, impregnation. The microwave pyrolysis provides fast heating rate and a short process time. Carbon fibre with favourable physicochemical and capacitive properties is obtained. Carbon fibre has high fixed carbon, surface area, and small fibres. Carbon fibre shows positive capacitive behaviour.